DESAIN BAHAN AJAR BERUPA HANDOUT BERBASIS INKUIRI TERBIMBING PADA PEMBELAJARAN KIMIA MATERI HIDROKARBON - Lina Wati; yuni fatisa (Konfigurasi : Jurnal Pendidikan Kimia dan Terapan, 2017)
AbstractThis research was instigated by students’ difficulty at the tenth grade of State Senior High School 10 Pekanbaru in comprehending chemistry concept of Hydrocarbon Lesson that made them unable to achieve optimal learning achievement, thus a teaching lesson was required to guide them to comprehend the concept.  It was done by designing a teaching lesson in the form of handout Guided Inquiry based.  This research aimed at knowing the validity and practicality levels of handout Guided Inquiry based that was valid and practical.  It was a Research and Development (R&D) with 4D (four-D) model, modified by doing limited trials and removing disseminating step.  It was administered at State Senior High School 10 Pekanbaru.  The primary data were collected in this research through questionnaire.  Validity and practicality test questionnaires were the instruments of collecting the data.  The data obtained were analyzed by using Descriptive qualitative and quantitative analysis techniques.  The handout produced was tested, its validity level was 89.94% (very valid) and its practicality level was 76.50% (practical).  Based on these results, it could be identified that the handout tested was appropriate and practical to be an alternative teaching lesson for teachers in a school. Keywords: Handout, Guided Inquiry, Hydrocarbon